# If $A$ and$I+AB$ are invertible, show $I+BA$ is also invertible

Show that if $A$ and $I+AB$ are invertible, then $I+BA$ is also invertible with $$(I+BA)^{-1} = A^{-1}(I+AB)^{-1}A$$

-
Multiply $I+BA$ on the left with $A^{-1}(I+AB)^{-1}A$ try to simplify it using the distributive property. Then do the same on the right. – Tim Seguine Jan 26 '13 at 22:13
Three answers, none from me, and yet mine is the only vote for the question so far. – Michael Hardy Jan 26 '13 at 22:16

Hint: Just do it. Use the fact that

$$(I + BA) A^{-1} = A^{-1} + B = A^{-1}(I+AB).$$

to show that

$$(I + BA) A^{-1} (I+AB)^{-1} A = I.$$

-
Is it also necessary to show $A^{-1} (I+AB)^{-1} A (I + BA)= I$? – mez Jan 26 '13 at 22:14
@mezhang For general square matrices $M, N$, if we know that $M N = I$, then $N M = I$. – Calvin Lin Jan 26 '13 at 22:16
@mezhang if a square matrix has a one sided inverse, then it has an inverse. CalvinLin: Your comment is only true for square matrices. – Tim Seguine Jan 26 '13 at 22:19
@Tim Could you show me a proof for your statement? I don't want to raise a separate question. Thanks. – mez Jan 26 '13 at 22:21
@mezhang Check the lemma in my answer here: math.stackexchange.com/questions/280884/… – Git Gud Jan 26 '13 at 22:22

$$(I + BA) = A^{-1}(I + AB)A \Rightarrow (I + BA)^{-1} = A^{-1}(I + AB)^{-1}A$$

-

Since $\,A^{-1}C^{-1}A=(A^{-1}CA)^{-1}\,$ , we get with $\,C=I+AB\,$ :

$$(I+BA)\left(A^{-1}(I+AB)^{-1}A\right)=(I+BA)(A^{-1}(I+AB)A)^{-1}=$$

$$(I+BA)(I+BA)^{-1}=I$$

-